2017
DOI: 10.1093/nar/gkx082
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge about the presence or absence of miRNA isoforms (isomiRs) can successfully discriminate amongst 32 TCGA cancer types

Abstract: Isoforms of human miRNAs (isomiRs) are constitutively expressed with tissue- and disease-subtype-dependencies. We studied 10 271 tumor datasets from The Cancer Genome Atlas (TCGA) to evaluate whether isomiRs can distinguish amongst 32 TCGA cancers. Unlike previous approaches, we built a classifier that relied solely on ‘binarized’ isomiR profiles: each isomiR is simply labeled as ‘present’ or ‘absent’. The resulting classifier successfully labeled tumor datasets with an average sensitivity of 90% and a false d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
188
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(202 citation statements)
references
References 96 publications
14
188
0
Order By: Relevance
“…However, it has already been shown that, in humans, these endpoint variations are constitutive in both healthy individuals and patients [10,24,25]. In fact, isomiRs have been shown to depend on a person's sex, population origin, and ethnicity [10,24], as well as on tissue, tissue state, and disease subtype [26,27]. Nontemplated nucleotide additions at the 3'-end can be due to nucleotide transferases (TUTase) that generally add adenine or uridine nucleotides [28].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has already been shown that, in humans, these endpoint variations are constitutive in both healthy individuals and patients [10,24,25]. In fact, isomiRs have been shown to depend on a person's sex, population origin, and ethnicity [10,24], as well as on tissue, tissue state, and disease subtype [26,27]. Nontemplated nucleotide additions at the 3'-end can be due to nucleotide transferases (TUTase) that generally add adenine or uridine nucleotides [28].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, post-transcriptional processing of miRNAs can generate nucleotide changes at any position of the sequence by RNA processing enzymes, such as A-to-I editing by ADAR enzymes [30]. The specific function of isomiRs is still not well understood, but multiple studies have suggested a context-specific effect of isomiRs on gene regulation [26,28,31,32]. This is further supported by the fact that different isomiRs from the same mature miRNA can target virtually non-overlapping sets of transcripts [10,[33][34][35].…”
Section: Resultsmentioning
confidence: 99%
“…Growing evidence suggests that isomiRs are generated in a context-dependent manner and play physiologically relevant roles during developmental and pathological processes (Hinton et al 2014;Tan et al 2014;Guo et al 2016;Wang et al 2016). Notably, it was shown that isomiR profiles successfully classify diverse cancer types and, when combined with miRNA profiles, improve discrimination between cancer and normal tissues (Telonis et al 2015;Koppers-Lalic et al 2016;Telonis et al 2017), highlighting isomiRs as potential diagnostic biomarkers. Therefore, applying AQ-seq to biosamples may enhance the diagnostic power of sRNA-seq.…”
Section: Discussionmentioning
confidence: 99%
“…These isomiRs increase the complexity of correctly identifying and quantifying specific microRNA species. Specific isomiR patterns have been reported to stratify diseases, such as cancer 6 , suggesting that accurate measurement of specific isomiRs may have clinical utility. At present, RNA sequencing is the only technique able to accurately detect and quantify isomiRs.…”
Section: Introductionmentioning
confidence: 99%